FACTORS ASSOCIATED WITH BLINDNESS AMONG DIABETIC PATIENTS ATTENDING MITYANA GENERAL HOSPITAL. A CROSS-SECTIONAL STUDY. - KISITU, ALEX; KABASA, MICHAEL (Student's Journal of Health Research Africa, 2024)
Background. Diabetes is on the rise as it is no longer a disease of predominantly rich nations. Diabetic-associated eye disease is steadily increasing everywhere, most markedly in the world’s middle-income countries including Uganda. This study assessed the factors associated with blindness among diabetic patients attending Mityana General Hospital. Methodology. A descriptive cross-sectional study design was adopted using a quantitative method of data collection. The study was conducted in Mityana district at Mityana General Hospital, data was collected using a structured questionnaire among 80 respondents. A probability sampling technique was used. Results. 39 (48%) respondents were between the ages of 41 and 60, and 48 (60%) were females only. Salary was a major economic factor, and 42(52%) of the respondents earned less than UGX 100,000. 46 (57%) of the respondents were farmers by occupation. Physical inactivity was a serious lifestyle factor discussed, with 28 (35%) respondents rarely engaging in physical activities and only 13 (16%) engaging in daily physical activity. Conclusions. Females were most affected by blindness due to diabetic eye disease and most of the respondents are of ages 41-60 years and many are farmers by occupation. In addition, the results agreed that the highest percentage rarely engaged in physical activity. Recommendations. The government, through the Ministry of Health, should fund free screening of diabetic patients for diabetic-related eye complications, especially from their communities through outreaches. In addition, sensitization and education on lifestyle modification and behavior can end blindness due to diabetic-related eye disease.